Efektivitas Dukungan Teman Sebaya dan Art Therapy terhadap NSSI SMK Citra Medika Gender - Sumarni D.W.; Andrian Fajar Kusumadewi; Erlin Erlina; Nafisa Rahma Khairani; Elfrida Twinsani Eggelion Missi; Purwanta Purwanta; Retno Adi Winarni (Pusat Studi Wanita dan Keluarga UGM, 2026)
Adolescent mental health is an urgent issue due to the rising prevalence of depression, anxiety, and Non-Suicidal Self-Injury (NSSI), which increases the risk of suicide and decreases overall well-being. Efforts to improve adolescent mental health aligned with SDG target 3.4, which aims to reduce premature mortality from non-communicable diseases through prevention and the promotion of mental health and well-being. This study aimed to examine the effectiveness of peer social support and art therapy in reducing NSSI behaviors among 60 students at SMK Citra Medika Magelang using a quasi-experimental pre–post-test design with a control group. The intervention consisted of training 20 students in peer support and art therapy through role-play and dance, who then implemented these approaches to 40 additional students, while the control group received counseling teacher assistance combined with similar art therapy. Data were analyzed using t-tests and linear regression, supported by in-depth interviews. The findings showed that the intervention group experienced a significant reduction in NSSI scores (t = 6.52; p = 0.00), while the control group also showed improvement but to a lesser extent (t = 6.33; p = 0.00). Overall, structured peer support enhanced the effectiveness of art-based interventions in reducing depressive symptoms and self-injurious behavior among adolescents.